2003
DOI: 10.1038/sj.onc.1206785
|View full text |Cite
|
Sign up to set email alerts
|

Functional inactivation of Cdk9 through oligomerization chain reaction

Abstract: The oligomerization chain reaction (OCR) strategy is a recently described technique for inactivation of target proteins that function as homoassociate complexes. This novel strategy is based on the fusion of self-associating coiled-coil (CC) domain of the nuclear factor promyelocytic leukemia (PML) to target proteins. Here, we present the successful application of the OCR strategy for inactivation of the heterodimeric Cdk9/cyclin T1 complex. Cyclin T1/Cdk9 (P-TEFb) complex is a positive regulator of gene trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Several studies from other laboratories suggest that P-TEFb is a potential therapeutic target. Anchorage-independent colony formation of HeLa cells and H1299 (lung cancer) cells is inhibited though oligomerization chain reaction (OCR)-mediated inactivation of CDK9 (Napolitano et al, 2003). Flavopiridol, a drug currently in clinical trials as a possible cancer therapy agent, is a very potent inhibitor of P-TEFb activity (Chao and Price, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies from other laboratories suggest that P-TEFb is a potential therapeutic target. Anchorage-independent colony formation of HeLa cells and H1299 (lung cancer) cells is inhibited though oligomerization chain reaction (OCR)-mediated inactivation of CDK9 (Napolitano et al, 2003). Flavopiridol, a drug currently in clinical trials as a possible cancer therapy agent, is a very potent inhibitor of P-TEFb activity (Chao and Price, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the oligomerization reaction induced by the CC domain of PML could lead to the formation of aberrant, nonfunctional high-molecular mass complexes, both when this domain is fused to proteins that are able to self-associate (5), as well as when the target of the OCR is a heterooligomer (6). We investigated whether the Pax8/TTF-1 heterocomplex could be targeted by the OCR strategy.…”
Section: Generation Of a Dominant-negative Pax8 Protein By Ocrmentioning
confidence: 99%
“…This property of the CC domain suggested that the presence of this region could be used to modify the function of a target protein. Indeed, two recent reports describe the OCR as an innovative strategy for the inactivation of target proteins that are able to self-associate (5) or that form heterocomplexes (6).…”
mentioning
confidence: 99%
“…In many cases, the loss of the oligomerization domain correlates with the loss of transforming properties by the chimeric proteins (32)(33)(34)(35)(36). Furthermore, the substitution of the self-interaction domain with a heterologous oligomerization module recapitulates the transforming potential of the primary chimeric protein (33) and inactivates known target genes (37,38). Therefore, it is thought that oligomerization of chimeric proteins is required for their oncogenic potential.…”
Section: Introductionmentioning
confidence: 99%